Rekam jejak dokter pejuang dan pelopor kebangkitan nasional HM. Nasruddin Anshoriy Ch, Djunaidi Tjakrawerdaya ; editor, Ken Z. Humaidi. - NASRUDDIN ANSHORIY Ch, HM; Junaidi Tjakrawerdaya; Ken Z. Humaidi (LKis, 2008)
xlvi, 194 hlm. ilus. 21 cm (3 eks.)